MORAL SUCCESS AND FAILURE IN THE ETHICAL THEORY OF TASAN CHŎNG YAGYONG - Baek, Min Jeong (Acta Koreana, 2016)
This study analyzes factors associated with moral success and failure in the ethical theory of Chŏng Yagyong (1762–1836), better known as Tasan. According to researchers who emphasize the cognitive and conative role of moral sentiments, moral success is ultimately driven by Tasan’s “moral mind” or “innate moral inclination.” According to them, moral sentiments are not blind, capricious feelings, but are able to intuitively perceive and discern good and evil; only by faithfully following one’s innate inclination toward good, is one well on the road to moral success. Tasan, however, in analyzing criminal acts in Hŭmhŭm sinsŏ (欽欽 新書; A new book on criminal law), notices a curious kind of moral failure caused by a strong moral emotion or passion toward socially endorsed moral virtues such as loyalty, filial piety and fidelity. Without much reflection on one’s inner mind or consideration on the proper method of one’s action, people fall prey to their “moral” emotions and commit crimes like taking revenge on the wrong person or committing suicide for the wrong reason. In his ethical theory, naturally, Tasan emphasizes not only moral sentiments and willpower but also the judging and weighing function of the mind, i.e., the cogitative mechanism of the spirit called kwŏnhyŏng (C. quanheng 權衡), literally meaning weighing and balancing. In this article, I attempt to describe the cogitative function of kwŏnhyŏng as judgment and decision and conclude that it is the actual and essential moral agency in Tasan’s ethical theory. Kwŏnhyŏng estimates and judges the issue at hand by inferring principles (K. ch’uri; C. tuili 推理), which is reminiscent of the rational and intellectual inference in Thomism. Although Tasan’s ethical theory was much influenced by Thomistic tradition, Tasan uniquely interprets “inferring the principle” as “inferring others’ minds from one’s own” (K. ch’usŏ; C. tuishu 推恕), which is a purely Confucian notion distinct from that presumed by Jesuit missionaries.